Phosphate rebinding induces force reversal via slow backward cycling of cross-bridges - Stehle, Robert (Frontiers in Physiology, 2025)
ObjectivePrevious studies on muscle fibers, myofibrils, and myosin revealed that the release of inorganic phosphate (Pi) and the force-generating step(s) are reversible, with cross-bridges also cycling backward through these steps by reversing force-generating steps and rebinding Pi. The aim was to explore the significance of force redevelopment kinetics (rate constant kTR) in cardiac myofibrils for the coupling between the Pi binding induced force reversal and the rate-limiting transition f– for backward cycling of cross-bridges from force-generating to non-force-generating states.MethodskTR and force generation of cardiac myofibrils from guinea pigs were investigated at 0.015–20 mM Pi. The observed force-[Pi], force-log [Pi], kTR-[Pi], and kTR-force relations were assessed with various single-pathway models of the cross-bridge cycle that differed in sequence and kinetics of reversible Pi release, reversible force-generating step and reversible rate-limiting transition. Based on the interpretation that kTR reflects the sum of rate-limiting transitions in the cross-bridge cycle, an indicator, the coupling strength, was defined to quantify the contribution of Pi binding induced force reversal to the rate-limiting transition f– from the [Pi]-modulated kTR-force relation.ResultsIncreasing [Pi] decreased force by a bi-linear force-log [Pi] relation, increased kTR in a slightly downward curved dependence with [Pi], and altered kTR almost reciprocally to force reflected by the kTR-force relation. Force-[Pi] and force-log [Pi] relations provided less selectivity for the exclusion of models than the kTR-[Pi] and kTR-force relations. The kTR-force relation observed in experiments with cardiac myofibrils yielded the coupling strength +0.84 ± 0.08 close to 1, the maximum coupling strength expected for the reciprocal kTR–force relationship. Single pathway models consisting of fast reversible force generation before or after rapid reversible Pi release failed to describe the observed kTR–force relation. Single pathway models consistent with the observed kTR-force relation had either slow Pi binding or slow force reversal, i.e., in the consistent single pathway models, f– was assigned to the rate of either Pi binding or force reversal.ConclusionBackward flux of cross-bridges from force-generating to non-force-generating states is limited by the rates of Pi binding or force reversal ruling out other rate-limiting steps uncoupled from Pi binding induced force reversal.